Effect of Pregnancy Stages on Changes in Lipid Profiles - Musa, Marwah Isam Sulaiman (Journal for Research in Applied Sciences and Biotechnology, 2023)
Defines Pregnancy is a physiological process occurring among women and female mammals; it usually begins with the process of fertilization of one egg or more, and the evolution of the atom inside the mother's womb is called a fetus or Embryo and continues the development of the fetus inside the mother until the birth. Usually, Pregnancy in women Aly40-36 continues)) almost a week after the end of the last menstrual cycle, more studies on Pregnancy in which women took the biggest in the research and investigation share, compared with studies conducted on female mammals. Pregnancy might result through a traditional male-female partnership or using cutting-edge medical technology. Nevertheless, the fetus grows and develops inside the mother's womb. Pregnancy is associated with major changes inside lipid profiles During Pregnancy. This study aimed to determine the level of triglycerides (T.G.), high-density lipoprotein (HDL), total Cholesterol (T.C.), low-density lipoprotein (LDL) and VLDL levels in the third trimester of Pregnancy in Tikrit city pregnant women. Ninety blood samples were taken at various times throughout Pregnancy for this prospective investigation. The analysis of variance was used to look at the data, and a significance level of p 0.05 was used. The results showed that the concentration of Cholesterol increased significantly with the progression of Pregnancy, as it was higher in the second and third stages of Pregnancy compared to the first stage of Pregnancy, while no significant differences were shown in the concentration of high-density lipoprotein (HDL) and low-density lipoprotein (LDL) with the progression of Pregnancy. In contrast, the first and last stages of Pregnancy were significantly superior in the concentration of VLDL and triglycerides (T.G.) compared to the second stage of Pregnancy. Delayed T.G. When high blood pressure in Pregnancy is combined with raised blood T.G. levels, a condition known as preeclampsia may develop. This correlation has the potential to provide light on the pathophysiology of preeclampsia and inform the design of interventions aimed at its early identification and prevention.